2015
DOI: 10.1017/jpa.2015.65
|View full text |Cite
|
Sign up to set email alerts
|

First fossil jacobsoniid beetle (Coleoptera):Derolathrus groehnin. sp. from Eocene Baltic amber

Abstract: Jacobsoniidae, comprising a small group of small-to-minute polyphagan beetles, is a family presently placed within Derodontiformia. No fossil jacobsoniid has been described to date. Here, we describe the first fossil jacobsoniid,Derolathrus groehnin. sp., based on two well-preserved individuals in middle Eocene Baltic amber. Micro–computed tomography (micro-CT) was used to reveal many diagnostic characters of the Recent genusDerolathrusSharp.Derolathrus groehniis compared with modernDerolathrusspecies and is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Species with the eye or wing reduction or atrophy are known in some of these groups at present, but are unknown from Baltic amber so far. In the contrary, Derolathrus groehni CAI, LESCHEN, LIU & HUANG, 2016 from Baltic amber is described as an unusually macrophthalmous representative of the extant genus (CAI et al 2016). Istrisia vithlandica sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species with the eye or wing reduction or atrophy are known in some of these groups at present, but are unknown from Baltic amber so far. In the contrary, Derolathrus groehni CAI, LESCHEN, LIU & HUANG, 2016 from Baltic amber is described as an unusually macrophthalmous representative of the extant genus (CAI et al 2016). Istrisia vithlandica sp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, numerous tiny, full-winged species with well-developed eyes of Aderidae, Cryptophagidae, Jacobsoniidae, Latridiidae, Monotomidae, Melandryidae, Salpingidae etc. were recorded from Baltic amber (ALEKSEEV & BUKEJS 2012REIKE 2012;LYUBARSKY & PERKOVSKY 2013;ALEKSEEV & GRZYMALA 2015;BUKEJS & ALEKSEEV 2015a, b;CAI et al 2016). Species with the eye or wing reduction or atrophy are known in some of these groups at present, but are unknown from Baltic amber so far.…”
Section: Discussionmentioning
confidence: 99%
“…Their particular distribution is understood as the result of long-distance dispersal, which is a natural dispersal mechanism in the family. It is facilitated by air currents, aided by the beetles’ feather-like hind wings and small body size 16 , 21 . Since some species appear to feed on fungi in soil and would naturally occur in association with soil on plant roots and in leaf litter, it has been suggested that their distribution pattern may be associated with anthropogenic causes, such as navigation or the introduction of plant species from many parts of the tropical world 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this explanation remains unsatisfactory and raises the question of why their long-distance dispersal by means of natural or anthropogenic mechanisms would be restricted to islands or isolated land areas rather than entire continents. On the other hand, it is possible that the beetles had a much wider distribution in the past, and the current endemism is due to regional extinctions, combined with new colonisations 6 , 16 . A divergence time analysis, calibrated using fossil data, revealed an Early Jurassic origin of Jacobsoniidae, at which time they split from their sister families Ptiliidae and Hydraenidae 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation